Evaluasi Efisiensi Teknik Sektor Publik di Kabupaten Banyumas - Barokatuminalloh Barokatuminalloh (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2008)
Health and Education expenditure are two important public spending items, those sectors playing important role at human capital development. Public subsidies for social services such as education and health care rest on two basic policy objectives: efficiency and equity. Efficiency gains can be achieved when the subsidies produce external benefits or correct for a market failure. The reseach aim is how to know the technical efficiency of health and education sector in every region at Banyumas Regency. This research uses secondary data with observation period 2007. The analysis instrument used in this research is DEA. The result of the research showing in general that the level of health efficiency sector in every region in Banyumas Regency is high enough. The level of efficiency for 17 regions from 27 regions is 100 percent. While the level of education efficiency sector in every region in Banyumas Regency is inefficient. The level for 16 regions from 27 regions is less than 100 percent. Keywords: public sector, technical efficiency , DEA